Pelatihan Senam Ergonomik Pada Lansia Dengan Hipertensi di Kelurahan Pondok Ranggon - Yuli Astuti; Nova Riani; Uum Safari; Dhien Novita Sani; Neneng Elviana; Irsan (Sagamedia Indo Press, 2022)
Introduction: Hypertension is a condition where a person's systolic blood pressure reaches 140 mmHg and diastolic blood pressure is more than 90 mmHg. Hypertension in the elderly is related to the aging process, at this old age usually a person will experience a loss of muscle strength, nervous system, and tissue so that the body does not function little by little. The elderly will experience changes in the cardiovascular system in the form of decreased elasticity in peripheral tissues and the occurrence of dilation of blood vessels and atherosclerosis, therefore the prevalence of hypertension in the elderly is very high. Objectives: The purpose of community service is to teach the elderly about ergonomic exercise that can help reduce blood pressure in the elderly. partners in this community service are the elderly from RT 09 RW 04 from the Pondok Ranggon family. Method: The method used in this community service is health counseling & training for the elderly in RT 09 RW 04 from the Pondok Ranggon family. Result: After being given health education, it was found that there was an increase in participants' knowledge from 70% to 80%. After being given ergonomic exercise, the average decrease in participants' blood pressure was 137.32 mmHg. These results prove that there is a need for health education through education and training in ergonomics to reduce blood pressure. These results prove that there is a need for health education through education and training in ergonomics to help lower blood pressure.